2020
DOI: 10.7759/cureus.8935
|View full text |Cite
|
Sign up to set email alerts
|

Tinea Corporis Masquerading as a Diffuse Gyrate Erythema: Case Report and a Review of Annular Lesions Mimicking a Dermatophyte Skin Infection

Abstract: Tinea is a superficial fungal infection of the skin. Gyrate erythemas are reactive conditions that present as annular red lesions. A 61-year-old woman was diagnosed with tinea corporis whose skin lesions morphologically mimicked a gyrate erythema. She presented with diffuse annular plaques affecting the left side of her chest and abdomen that did not respond to a combination antifungal-corticosteroid cream for six-month duration. The appearance and clinical differential diagnosis included a gyrate erythema. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In the current case, EGR was suspected due to the patient’s risk factors for gastro-oesophageal cancer ( 3 , 7 ). EGR is, however, characterized by rapidly migrating lesions, and the patient had no anaemia, weight loss, or cancerous lesions on total-body tomography ( 7 ).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In the current case, EGR was suspected due to the patient’s risk factors for gastro-oesophageal cancer ( 3 , 7 ). EGR is, however, characterized by rapidly migrating lesions, and the patient had no anaemia, weight loss, or cancerous lesions on total-body tomography ( 7 ).…”
mentioning
confidence: 86%
“…Because of its unusual appearance, tinea incognita is difficult to diagnose and should be suspected in cases of aspecific, erythematous, pruritic patches, in which the typical ringworm appearance of tinea is minimal ( 3 ).…”
mentioning
confidence: 99%
“…The frequent use of combination creams of antifungal with potent topical steroids (such as clotrimazole/betamethasone) to treat undiagnosed dermatitis can lead to TI. 8,9 Iraq studies found that the topical steroid abuse by a patient or doctor can provide strong possible explanations for the epidemic of resistant dermatophytosis. 10 Some other factors may play a role in chronicity of superficial fungal infections and lead to the development of TI.…”
Section: Causesmentioning
confidence: 99%
“…The differential diagnosis includes other granulomatous and annular diseases such as tinea corporis, leprosy, tuberculosis, sarcoidosis, granuloma annulare and necrobiosis lipoidica. 6 The histopathological analysis is crucial for a correct diagnosis. Mycotic and mycobacterial cultures may also be necessary to exclude infectious diseases.…”
mentioning
confidence: 99%